Assessing the poultry farmers intention to adopt Insects as alternative chicken feed - Wong, K. K. S.; Khazali, N. F. (Malaysian Society of Animal Production (MSAP), 2023)
Due to the weakening of the Malaysian ringgit and the rise in global feed prices, the cost of poultry feed has recently risen dramatically in Malaysia. This study investigates the elements that influence farmers' intentions to replace soybeans and corn with insects. The questionnaire survey was completed by 52 poultry farmers using the snowball sampling approach. The Theory of Planned Behaviour and factor analysis were used in this study to examine the impact of farmers' attitudes, subjective norms, and perceived behavioural control on their intention to utilize insects as maize and soybean substitute feed. The component analysis revealed that farmers' views toward substitute feed, subjective standards, and perceived behavioural control are critical factors in explaining their intentions. This study suggested that farmers are eager to accept alternative feed for their farming if the insects used to replace conventional feed are ecologically benign, low-cost, safe, and sustainable.